School poverty effects on trajectories of child behaviour: Do they depend on gender and ethnicity?. (July 2017) - Midouhas, Emily
Abstract: This study examined English school poverty effects on trajectories of child behaviour across ages 3, 5, 7 and 11, and the moderating roles of ethnicity and gender. School poverty predicted internalising and externalising problems concurrently, and internalising problems longitudinally. In poor schools, girls had a steeper incline in internalising problems, but made greater reductions in externalising problems. Ethnic differences were also found in the association between school poverty and child adjustment. Gender and ethnic background may influence how a child responds emotionally and behaviourally to the composition of peers at school. Highlights: School poverty effects on child behaviour by gender and ethnicity are tested. School poverty predicted internalising and externalising problem trajectories. Girls' internalising and boys' externalising problems worsened in poor schools. Ethnic differences were found in the school poverty and child adjustment association.